2012
DOI: 10.4103/1658-354x.101224
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypertension and pulmonary edema associated with systemic absorption of topical phenylephrine in a child during retinal surgery

Abstract: Topical phenylephrine solutions are widely used in eye procedures to promote pupil dilation without cycloplegia. We report a case of intraoperative severe hypertension and acute pulmonary edema occurring in a child during retinal surgery after possible systemic absorption of topical phenylephrine eyedrops. Our objective is to discuss the proper treatment and preventive strategies for such a complication. A 4-year-old, male patient, 18.4 kg in weight, physical status ASA I was admitted for right retinal detachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A 2015 systemic review and metanalysis that included 916 participants showed that, in the adult population, 2.5% phenylephrine eye drops did not lead to clinically relevant change in blood pressure and heart rate, and 10% phenylephrine collyrium caused only short-lived blood pressure and heart rate rise [12]. Severe adverse events to phenylephrine collyrium are described mainly in relation to ophthalmological procedures, as reported by Abdelhalim et al [13]. The authors described the case of a 4-year-old boy who developed severe hypertension and acute pulmonary edema during retinal surgery (i.e., after surgical incision of the eye) due to systemic absorption of topical phenylephrine eye drops.…”
Section: Discussionmentioning
confidence: 97%
“…A 2015 systemic review and metanalysis that included 916 participants showed that, in the adult population, 2.5% phenylephrine eye drops did not lead to clinically relevant change in blood pressure and heart rate, and 10% phenylephrine collyrium caused only short-lived blood pressure and heart rate rise [12]. Severe adverse events to phenylephrine collyrium are described mainly in relation to ophthalmological procedures, as reported by Abdelhalim et al [13]. The authors described the case of a 4-year-old boy who developed severe hypertension and acute pulmonary edema during retinal surgery (i.e., after surgical incision of the eye) due to systemic absorption of topical phenylephrine eye drops.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism described included increased systemic vascular resistance resulting in increase in left ventricular ejection impedance and end-diastolic volumes and pressures. [11] ECT produces an acute dose-dependent increase in plasma norepinephrine levels and BP. [12] Studies in acute subarachnoid haemorrhage-induced pulmonary oedema have also shown a similar increase in plasma catecholamine levels.…”
Section: Discussionmentioning
confidence: 97%
“…This association of having co-morbid conditions has also been pointed out in previously published case reports. [ 4 , 5 , 8 ] In the previous case reports published,[ 9 , 10 ] one of the important reasons for the development of PE was the topical administration of phenyl epinephrine eye drops. Our dataset has no history of documented administration of these drops.…”
Section: Discussionmentioning
confidence: 99%